The Z-2018 emissions inventory of COS in Europe: A semiquantitative multi-data-streams evaluation. (1st May 2023) - Belviso, Sauveur; Pison, Isabelle; Petit, Jean-Eudes; Berchet, Antoine; Remaud, Marine; Simon, Leïla; Ramonet, Michel; Delmotte, Marc; Kazan, Victor; Yver-Kwok, Camille; Lopez, Morgan
Abstract: The anthropogenic emissions of carbonyl sulfide (COS) and the uptake of this gas by terrestrial vegetation are major drivers of COS concentration variations in the atmosphere since the beginning of the industrial era. The fine spatial resolution (i.e., 0.1° × 0.1°) of the gridded anthropogenic emissions inventory of COS developed by Zumkehr et al. (2018), Z-2018 hereafter, is designed for a use by regional chemistry-transport models. In order to anticipate future applications at the regional scale, we carried out a first semiquantitative assessment of direct and indirect (i.e., from CS2 conversion) COS anthropogenic emissions at the sub-country scale in France using historical governmental data. Better agreement between the two inventories was found for direct emissions of COS by coal power plants, than for indirect sources. The use in this latter case of a sub-country spatial scaling, based on industrial N2 O emissions, (1) strongly underestimates fluxes from food casings and cellulosic sponge industrial activities responsible for atmospheric CS2 emissions in France, and (2) considerably overestimates emissions from Paris and surrounding areas, which are free of a rayon industry. A list of food casings and cellulosic sponge industrial sites is provided to produce a more realistic inventory of CS2 sources in Europe. Nevertheless, a cluster analysis of wintertime air masses trajectories, with the atmospheric COS monitoring site of Gif-sur-Yvette (GIF) as end point, suggests that Z-2018 correctly identifies northern Germany and Belgium as sources of anthropogenic COS. In winter, when the wind blows from the NE sector, advection of anthropogenic COS from coal power plants is illustrated by synchronous variations in GIF and at the Trainou tall tower (distant of about 80 km) of a series of atmospheric pollution tracers, especially between COS and sulfates. These observations support the use of SO2 emissions as temporal and sub-country spatial scaling factors of COS emissions by the coal industry. Highlights: We evaluate the European gridded anthropogenic emissions inventory of carbonyl sulfide (COS). The monitoring site of Gif-sur-Yvette (GIF, FR) has observations back to 2014. With GIF as end point, cluster analysis of winter air masses trajectories show that FR is not a net COS source. The existing inventory largely overestimates French COS emissions by about one order of magnitude. Perspectives are drawn as to the way this inventory should be revised.